Energy balance determination of crop evapotranspiration using a wireless sensor network - Jimenez-Berni, Jose A.; Cabello-Leblic, Arantxa; Lopez-Guerrero, Alicia; Villalobos, Francisco J.; Testi, Luca; Fereres, Elias (Frontiers in Agronomy, 2023)
Determining crop evapotranspiration (ET) is essential for managing water at various scales, from regional water accounting to farm irrigation. Quantification of ET may be carried out by several procedures, being eddy covariance and energy balance the most established methods among the research community. One major limitation is the high cost of the sensors included in the eddy covariance or energy balance systems. We report here the development of a simpler device (CORDOVA-ET: COnductance Recording Device for Observation and VAlidation of ET) to determine crop ET based on industrial-grade, commercial off-the-shelf (COTS) sensors costing far less than research-grade sensors. The CORDOVA-ET contains a sensor package that integrates the basic micrometeorological instrumentation and the infrared temperature sensors required for estimating ET over crops using the energy balance approach. One novel feature is the presence of four different nodes that allow the determination of ET in four different locations within a field or in four different fields of the same crop, thus allowing an assessment of ET spatial variability. The system was conceived as an open-source and hardware alternative to commercial devices, using a collaborative approach for the development of a regional ET network in countries of North Africa and the Near East. Comparisons of radiation, temperature, humidity, and wind against those of research-grade sensors yielded excellent results, with coefficients of correlation (R 2 ) above 0.96. The estimated reference ET calculated from these measurements showed R 2 =0.99 and a root mean square error (RMSE) of 0.22 mm/day. The infrared temperature measurements at the four different nodes showed an RMSE below 0.56 • C. The energy balance components and estimates of ET from the CORDOVA-ET were validated against an eddy-covariance system over a wheat crop. The high (R 2 ) for net radiation (0.98), sensible heat (0.88), and latent heat (0.86) showed good agreement between the modeled energy fluxes and the field measurements. The hardware components, acquisition, and data processing software are available as open-source repositories to facilitate adoption for different applications, from water use efficiency research to irrigation management.